Expert assessment and consumer preferences for the implementation of educational tourism in the learning system of universities students: the experience of Kazakhstan - Tashenova, L.; Mamrayeva, D.; Borbasova, Z. (Economic Annals-XXI, 202(3-4), 108-126., 2023)
Our research is devoted to the implementation of educational tourism in the education system of higher education students, identifying the prospects for its development based on expert and consumer surveys. The article proposes the author’s definition of educational tourism, reveals its essence and component composition, as well as possible positive effects from its implementation; the connection between the educational and tourist components is emphasized, the primary and secondary nature of which is determined by motivational factors. The key directions for the development of educational tourism are identified through the study of current works presented in the scientometric databases WoS and Scopus. We conducted a study of the main participants in the educational tourism market in Kazakhstan, in particular, we analyzed the indicators of academic mobility of students and employees of scientific and educational institutions; international activities of universities in countries; as well as the number of students, teaching staff in organizations of technical and professional, higher and postgraduate education. The examples of educational tours provided by travel agencies in Kazakhstan are shown. Based on expert surveys and polls, the features of consumer demand and supply in the field of educational tourism were identified, as well as the main communication channels for promoting this product on the market; main promising directions for the development of educational tourism; the degree of awareness of students of higher educational institutions about the essence and specifics of educational tourism; the need to include educational tourism in the educational trajectory of university students. In terms of the characteristics of consumption and provision of services in the field of educational tourism, the authors identified: seasonality and frequency of consumers’ requests to obtain information, form and arrange an educational tour; key motivational factors that guide consumers when choosing an educational tour; average duration and geographic focus of organized educational tours; problems that travel companies face when designing and organizing such tours. In terms of the selection of information and communication tools used to promote educational tours, the main and additional communication channels for promoting educational tours have been identified. In terms of identifying the main promising directions for the development of educational tourism, the average expert assessment of the level of development of outbound and inbound educational tourism was determined. Experts proposed the main promising directions for the development of educational tourism in Kazakhstan, including studying abroad, participation in educational events, learning foreign languages and ecological tours with a scientific focus; the need to include educational tourism in the educational process of university students is emphasized.
Keywords: Educational Tourism; Learning Trajectory; Tourism Economics; Activities of Travel Companies; Student-Centered Education; Customized Tourism Product; Academic Mobility